Effect of Starter Amount to Sensory Characteristics Score of Fruit Yogurt - Yessita Puspaningrum; Miftachul Chusnah; Nurul 'Aini; Ana Mariatul Khiftiyah; Dyah Ayu Sri Hartanti; Anggi Indah Yuliana; Agus Suhadi (AGARICUS: Advances Agriculture Science & Farming, 2023)
Fruit yogurt is a food product in the form of processed milk through a fermentation process using Lactobacillus bulgaricus and Streptococcus thermophilus bacteria, added with fruits. Yogurt quality is determined by the amount of starter added. This study aims to determine the effect of the amount of yogurt starter on the sensory characteristics score of watermelon, melon and golden melon yogurt. Three various amounts of yogurt starter were used in this research, namely 2%, 4%, and 6%. The starter was purchased from yogurt sold in the market. The starter consisted of Streptococcus thermophilus, Lactobacillus bulgaricus, L. acidophilus, and Bifidobacterium. Sensory properties consisting of color, aroma, texture and taste, were assessed by ten panelists by giving a score between 1-5. The results showed that the concentration of the starter could provide different scores of sensory characteristics. Watermelon yogurt made with 4% starter got the highest score for color, while the highest score for aroma was obtained by watermelon yogurt made with 6% starter. Watermelon yogurt made with 6% starter also got the highest score for texture, along with golden melon made with 4% starter. Based on the taste, the highest sensory characteristics score was obtained by yogurt without fruit that had been made with 4% starter.